A Self-Directed Review of Anatomy Related to Local Anesthesia - Terry Dean (Association of American Medical Colleges, 2010)
Abstract Introduction This module contains a self-directed review of anatomy related to local anesthesia with emphasis on skull and anatomical considerations. The primary goal is to provide a focused review of relevant anatomy and landmarks to assist the dental or dental hygiene student in achieving success in taking a course on the delivery of local anesthesia. The material can be downloaded as a Word document or PDF file and includes an assessment and answer keys. It is designed for dental and dental hygiene students who will be taking a course in delivery of local anesthesia. Methods Utilizing available resources, texts, and previous coursework, students work through this handout and locate structures listed, answer pertinent questions, and are asked to visually locate landmarks and structures. It is of paramount import that a student be familiar with the anatomy associated with giving local anesthesia for several reasons: namely to achieve success in finding correct target sites of deposition of anesthesia, to avoid most complications related to anatomy, and overall better patient treatment to name a few. Results This exercise has been incorporated into a course on delivery of local anesthesia for dentistry 5 years ongoing. The first time it was initiated practical outcomes for students increased from a 91% pass rate to a 100% pass rate. Precourse surveys indicated that having knowledge of head and neck anatomy was not only important but few stated their knowledge was excellent and majority stated it needed improvement. Discussion This andragogical approach should assist students with desired learning outcomes of clinical coursework in delivery of local anesthesia, as often head and neck anatomy courses are presented in most curricula well ahead of local anesthesia course and a review of anatomy is warranted. Ideas for improvement would be to create an online version for self-directed study.